1999
DOI: 10.1155/s0161171299226373
|View full text |Cite
|
Sign up to set email alerts
|

On the vertical bundle of a pseudo‐Finsler manifold

Abstract: Abstract. We define the Liouville distribution on the tangent bundle of a pseudo-Finsler manifold and prove that it is integrable. Also, we find geometric properties of both leaves of Liouville distribution and the vertical distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…where the local components are expressed by Proof. Follows using an argument similar to that used in [4,22]. It can be found in [23] for a more general case when the manifold M is endowed with a Finsler structure.…”
Section: An Almost Contact Structure On the Vertical Liouville Distrimentioning
confidence: 95%
“…where the local components are expressed by Proof. Follows using an argument similar to that used in [4,22]. It can be found in [23] for a more general case when the manifold M is endowed with a Finsler structure.…”
Section: An Almost Contact Structure On the Vertical Liouville Distrimentioning
confidence: 95%
“…Following [3], [9] we define two vertical Liouville distributions on T M as the complementary orthogonal distributions in V 1 and V 2 to the line distributions spanned by the Liouville vector fields E 1 and E 2 , respectively. By (1.4) and (1.5) we have…”
Section: Vertical Liouville Distributions V E 1 and V Ementioning
confidence: 99%
“…The vertical Liouville distribution on the tangent bundle of a (pseudo) Finsler space was defined for the first time in [3] where some aspects of the geometry of the vertical bundle are derived via vertical Liouville distribution. A similar study on the cotangent bundle of a Cartan space can be found in [9].…”
Section: 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some problems specific for tangent manifolds can be extended and studied on the normal bundle of the lifted Finsler foliation. Firstly, following [4], we define a Liouville distribution in the vertical bundle and we prove that it is integrable. Next, by analogy with [2], some framed f (3, ε)-structures on the normal bundle of the lifted Finsler foliation are defined and studied in the paper.…”
Section: Introductionmentioning
confidence: 99%